The Biological, Sociological, And Ideological Aspects In The Children's Story “Pasawitran I Jangkrik Teken I Petani” - Putu Chrisma Dewi; Km Tri Sutrisna Agustia; Gek Wulan Novi Utami (Denpasar Institute, 2023)
Children's stories, especially Balinese stories, are one of the effective media to provide environmental education to children and introduce their mother tongue or regional language as early as possible as a form of language preservation. In addition, the introduction of stories to children from an early age will have an impact on children's love of literacy. This research analyses the environmental lexicon from an ecolinguistics perspective found in Balinese children's stories. This research aims to identify biological, sociological, and ideological aspects of Balinese children's stories. This is qualitative research, the data was taken from a Balinese children’s story entitled Pasawitran I Jangkrik Teken I Petani. The result shows that children can learn some environmental and farming-based lexicons in this story, which is very good and necessary for language preservation. Ideologically, children are invited to understand the importance of environmental protection and ecological balance. By applying these sociological aspects in the story Pasawitran I Jangkrik Teken I Petani children can learn about social dynamics, tradition, and social systems